KEEFEKTIFAN KONSELING KELOMPOK REALITAS MENGATASI PERSOALAN PERILAKU DISIPLIN SISWA DI SEKOLAH - Widodo, Bernardus (Widya Warta, 2011)
Discipline is an important part of education in the context of formal, non-formal, and informal education. Discipline can be seen as a positive and constructive power which is capable of providing any equipment to form consistency, predictability, enjoyment, and suitable environment of educating and learning. Discipline in truth is not the obedience toward the rule which is forced from out side, but it is such a self-reliance which is based on desire to make an order in life. The weakness of students’ self-reliance will impact to the wrong manner, which is called the problem of discipline, where students break the rules: playing truant, being late for school, making noise, gossiping, and cheating. Counseling as an integral part of education is responsible for handling students’ discipline at school through un-punishment ways. The real group counseling by William Glasser can be proposed as a model of counseling for counselors to improve students’ discipline in un-punishment way. This model is hoped to provide counselors with practicality to help students to control their better life to have real manner, and to be responsible. The quantitative with experiment design aimed to search the effectiveness of real group counseling in improving students’ manner at school, which was indicated by the increase of self-reliance and the decrease of students’ indiscipline. Operationally the development model of reality teraphy comprises procedure of real group counseling with WDEP model, which cover 6 steps: participation, wants exploration, direction and doing, evaluation, planning, and termination. The study found some improvement on the aspects of self reliance and the decrease of duration of students, indiscipline which was guessed as the impact of the treatment. In other words, the treatment given to the subject which was designed in the form of real group counseling was effective to improve students’ discipline at school.